Transformasi Gen Antisens ACC Oksidase pada Pepaya dengan Teknik Penembakan Partikel - Diani Damayanti; Sudarsono Sudarsono; Ika Mariska; Muhamad Herman (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2009)
Papaya (Carica papaya L.) is a climacteric fruit that exhibit avery fast ripening rate. Ethylene controls the ripening eventin the papaya fruit. 1-aminocyclopropane-1-carbocxylic acid(ACC) oxidase gene encodes a specific enzyme for ethylenebiosynthesis. The gene had become a target for manipulationto make a gene construct of an antisense ACC oxidaseto regenerate transgenic papaya that has a characteristic ofdelayed ripening. The objective of the experiment is to engineer transgenic papaya that has a delayed ripening characteristic by transforming papaya with the antisense ACC oxidase gene through particle bombardment technique. The immature embryos of papaya variety Burungwere used for the explants. Antisense ACC oxidase and reporter (gus) genes were co-transformed to papaya calli. Four hundreds eighteen calli were bombarded by the antisense ACC oxidase gene. The transformation experiment resulted 25 putatives transgenic plants out of fifty plantsacclimatized in a greenhouse. Gus gene expression assay observed at 9 days after bombardment showed that the papaya explants bombarded twice at 9 cm shoot distance had 53.3% transformation rate of gus positive and 5.25 blue spots number in average. The results of PCR analysis showed that four out of 25 transgenic putative papaya plants (TR6, TR9, TR20, dan TR24), indicated a positive PCR of the antisense ACC oxidase gene with the amplified fragment DNA size of 800 base pair.